Growth Strategy: A Conceptual Framework - Lee, Seung Joo (KDI School of Public Policy and Management, 2004)
Growth Strategy is one of the top CEO agenda in most corporations today. The main objective of this paper is to review the existing literature on growth and provide a conceptual framework for managers to think systematically about growth strategy. The framework consists of seven key questions that could be used as a diagnostic tool to focus attention and stimulate strategic thinking. Each question has been elaborated further with specific examples of successful growth companies.
Keywords: growth strategy; strategy formulation; strategic thinking